Be Kind to Your Mind : A pocket guide to looking after your mental health - Chamberlain, Claire (Writer on health) (London, UK : Vie Books, 2020)
Give your mind a little TLC. When our bodies aren't on top form, we rest and take care of them - but we often don't do the same for our minds. Whether it's because we don't know where to start, or because it never feels like a high enough priority, carving out time and space to care for our mental health can be hard. But it needn't be. With bite-sized tips and practical advice, this book makes self-care simple and achievable. From finding calm and thinking positively, to stress-busting and balancing your life, everything you need to know about taking care of you is wrapped up in this handy pocket guide, and will give you the tools to help you feel your best.
Calm Your Mind -- Embrace Mindfulness -- Stay Positive -- Look After Yourself -- Be Kind -- Balance Your Life -- Step Outdoors.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on print version record.
OCLC control number change
Keywords: Self-care, Health; Mental health -- Popular works; Electronic books